Use of copeptin for rapid rule-out of acute myocardial infarction - Müller, Christian; Giannitsis, Evangelos (European heart journal - acute cardiovascular care, 2018)
Copeptin is currently understood as a quantitative marker of endogenous stress. It rises rapidly in multiple acute disorders including acute myocardial infarction. As a single variable, it has only modest diagnostic accuracy for acute myocardial infarction. However, the use of copeptin within a dual-marker strategy together with conventional cardiac troponin increases the diagnostic accuracy and particularly the negative predictive value of cardiac troponin alone for acute myocardial infarction. The rapid rule-out of acute myocardial infarction is the only application in acute cardiac care mature enough to merit consideration for routine clinical care. However, the dual-marker approach seems to provide only very small incremental value when used in combination with sensitive or high-sensitivity cardiac troponin assays. This review aims to update and educate regarding the potential and the procedural details, as well as the caveats and challenges of using copeptin in clinical practice.
Gesehen am 06.05.2019
First published: June 8, 2017